The ongoing challenge of violence against women and children in South Africa. Why are we deeper in crisis? - Shahana Rasool (The Thinker)
Gender Based Violence (GBV) has been referred to as the Shadow Pandemic, since it has tripled internationally from the start of the outbreak of COVID-19. The increased rates of reported GBV around the globe have ranged from 30% to 200%. We have seen high numbers of GBV reports in SA as well, with the GBV toll-free emergency hotline reporting 120 000 calls in the first three weeks of lockdown.